Is Early Complement Activation in Renal Transplantation Associated with Later Graft Outcome? - Bobka, Steffen; Ebert, Nadja; Koertvely, Eloed; Jacobi, Johannes; Wiesener, Michael; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: Complement activation is important in post-transplantation renal injury, but data on its role as predictor of transplant outcome/complications when assessed in donor kidneys are lacking. METHODS: In human renal transplant biopsies with delayed graft function (DGF, n=12), antibody mediated rejection (ABMR, n=8), T-cell mediated rejection (TCMR, n=11), 1 year protocol biopsies (control, n=10) and corresponding zero-biopsies we performed immunohistochemical analyses of 6 complement factors using FFPE sections and correlated the findings with kidney function, as assessed by serum creatinine, and morphological changes including interstitial fibrosis and tubular atrophy (IF/TA). RESULTS: In DGF, TCMR and ABMR significant complement deposition was observed, which was less pronounced in corresponding zero-biopsies. Zero-biopsies with subsequent ABMR showed glomerular complement factor D and C3c expression. Moreover, glomerular C3c and C9 and tubular MASP-2 and Collectin-11 expression in zero-biopsies significantly correlated with serum creatinine at diagnosis of DGF, TCMR or ABMR. Glomerular C1q was significantly increased in ABMR, but not in DGF and TCMR. In contrast, peritubular C1q was significantly enhanced in DGF and TCMR compared to zero-biopsies. Using C3d as a surrogate marker for complement activity we could confirm that stained complement factors are frequently associated with complement activity. CONCLUSION: Complement deposition strongly correlated with histopathological changes observed in renal transplants. All 3 complement pathways were operational in biopsies with DGF, TCMR and ABMR albeit with differential abundance and localization. Since complement deposition in zero-biopsies correlated with graft function and morphological changes, early specific complement inhibition in renal transplantation may be a new therapeutic option to prevent graft loss.
EVALuna2:35394